Application of the Discovery Learning Model to Improve Students' Science Process Skills on Virus Material - Sela Restia Tangahu; Ani M. Hasan; Jusna Ahmad; Masra Latjompoh; Yuliana Retnowati; Ilyas Husain (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2024)
Based on the results of a researcher interview with one of the biology teachers at SMAN 3 Gorontalo, science process skills have been applied before, but in their implementation they do not get maximum results so that science process skills in students do not develop. The purpose of the study was to improve the science process skills of students who used the Discovery Learning model on virus material. This type of research is descriptive quantitative with Pre-Experimental Design research methods and One group pretest and posttest designs. The subjects in this study were 31 students of grade X-4 SMA Negeri 3 Gorontalo. The indicators of science process skills observed in this study consist of aspects of observing, interpreting, applying concepts, grouping, and communicating. The results obtained the average pretest score was 45.21%, and the average posttest score was 77.75%. From the results of the study, it can be concluded that the science process skills of grade X students of SMA Negeri 3 Gorontalo can be improved through the application of the Discovery Learning model